Novice English Teachers in Shock: Which factors are behind it? - Lopera, Merylein Higuita; Díaz, Ana Elsy (Íkala, Revista de Lenguaje y Cultura, 2015)
This paper reports on a research aiming to identify the factors that cause shock in novice English teachers during their first four years of service at public educational institutions in the city of Medellin. Following a qualitative-research approach and within the classical ethnographic interpretative framework, this research enrolled eight novice foreign language teachers, who graduated from Universidad de Antioquia between 2007 and 2009 and who, by the time of the study, were serving as basic education teachers at a public institution. The participants responded to a survey and participated in a focal group interview. Findings show that the shock experienced by novice English teachers is mainly caused by situations of violence in the socio-cultural context impacting the public educational institution, as well as lack of strategies to manage students ́ inappropriate behavior, lack of awareness about educational, linguistic and labor policies; lack of effective didactic strategies on foreign language teaching and learning and poor working relations with other teachers at the educational institution.